2010
DOI: 10.1007/s11897-010-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Observation Units in the Management of Acute Heart Failure Syndromes

Abstract: Observation units (OUs) for acute heart failure syndromes (AHFS) have proven to be effective in reducing heart failure admissions and may reduce costs. Goals for risk-stratifying patients with AHFS in OUs include determining patients suitable for OU management and determining end points of treatment. Although many provider models and settings exist, management algorithms common to most OUs include monitoring/nursing care, diagnostic procedures, therapy, and educational/social services. The focus of OU manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Accordingly, we suggest two sets of interventions that might facilitate optimal evidencebased observation services use. 2,[43][44][45][46][47][48] First, it seems sensible to establish clear criteria for placement in observation that focus on using observation to facilitate the admission-versusdischarge decision, rather than avoiding decisions under the guise of watchful waiting (recognizing that for some conditions like head injury, watchful waiting is itself an appropriate protocol). Simultaneously, once a patient is placed under observation, they must be approached with defined endpoints in mind, lest the extra time merely result in over-investigation and delayed admission or discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we suggest two sets of interventions that might facilitate optimal evidencebased observation services use. 2,[43][44][45][46][47][48] First, it seems sensible to establish clear criteria for placement in observation that focus on using observation to facilitate the admission-versusdischarge decision, rather than avoiding decisions under the guise of watchful waiting (recognizing that for some conditions like head injury, watchful waiting is itself an appropriate protocol). Simultaneously, once a patient is placed under observation, they must be approached with defined endpoints in mind, lest the extra time merely result in over-investigation and delayed admission or discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency physicians are skilled and well equipped to provide acute therapy for the first 24 to 48 hours for the patient with ADHF, thus making ED-based observation a logical and economical means to care immediately for this patient population. 8,65 OUs were identified by the Institute of Medicine as central to improving resource use and patient flow. A recent study 66 suggested that increased use of the OU has the potential to save $3.1 billion and avoid 2.4 million inpatient admissions.…”
Section: Dispositionmentioning
confidence: 99%
“…7 Because more than 80% of patients with ADHF present to the emergency department (ED), significant pressures exist to manage these patients efficiently in the acute-care environment. 8 Selected patients may be eligible to receive care for ADHF in an observation unit (OU), which may provide a safe and effective means to lower costs by providing an alternative to an inpatient stay. 9 Previous studies have suggested that more than 50% of such patients are appropriate for a brief period of observation and treatment aimed at avoiding inpatient admission.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1 million Americans with a primary diagnosis of heart failure (HF) are seen in emergency departments (ED) annually, with 70-80 % ultimately being admitted to the hospital [1,2]. For many patients, hospitalization for acute decompensated HF created a vicious cycle of HF ''revisits'' back to the ED and hospital [3].…”
Section: Introductionmentioning
confidence: 99%